Impact of WOM and Online WOM on Tourist Destinations in Indonesia - JIE-HUA, SIANG; WEN-GOANG, YANG; LI-WEI, LIU (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Online word-of-mouth, also known as e-WOM and Word of Mouth (WOM) are the most influential sources in the marketing sector. These information sources will be applied to the tourism sector. The results show that online WOM influence positively and significantly on destination image; online WOM is a positive and significant influence on the intention to visit; WOM is positive and not significant on the destination; WOM has a positive and significant influence on the intention to visit; destination has a positive and significant influence on the intention to visit. Implications and future research are discussed in this study. RESUMEN El Boca a Boca en línea, también conocido como e-WOM y el Boca a Boca (WOM) son las fuentes más influyentes en el sector del marketing. La información de estas fuentes se aplicará al sector turístico. Los resultados muestran que WOM en línea influye de forma positiva y significativa en la imagen del destino; WOM en línea es una influencia positiva y significativa en la intención de visitar; WOM es positivo y no significativo en el destino; WOM tiene una influencia positiva y significativa en la intención de visitar; el destino tiene una influencia positiva y significativa en la intención de visitar. En este estudio se discuten las implicaciones y la investigación futura.